Metal-phenolic nanozyme as a ferroptosis inhibitor for alleviating cisplatin-induced acute kidney injury - Xiong, Yunfeng; Kang, Huimin; Rao, Yanping; Huang, Xiayu; Zhu, Yang; Wei, Lixin (Frontiers in Pharmacology, 2025)
IntroductionCisplatin-induced acute kidney injury (AKI) is primarily caused by oxidative stress from reactive oxygen species (ROS) accumulation. Developing ROS scavengers presents promising opportunities for preventing and treating this condition by targeting oxidative stress mechanisms.MethodsThis study involves the fabrication of a metal-polyphenol self-assembled nanozyme (Fe@Ba) designed to inhibit ferroptosis through synergistic catalytic actions and antioxidant properties. The nanozyme is constructed using metal-polyphenol coordination-driven nanoprecipitation techniques. Its performance is evaluated in vitro using MTEC cells and in vivo within an AKI model, with assessments of catalytic activities, ROS depletion efficacy, antioxidant effects, and anti-ferroptotic mechanisms.ResultsThe Fe@Ba nanozyme demonstrates significant catalase (CAT) and superoxide dismutase (SOD)-like activities upon internalization by MTEC cells, effectively reducing high ROS levels in the AKI model. Baicalein (Ba), a traditional Chinese medicine component in the nanozyme, exhibits strong antioxidant properties, inhibits lipid peroxidation (LPO), upregulates reductive glutathione (GSH), and promotes glutathione peroxidase 4 (GPX4) expression, thereby inhibiting ferroptosis. Fluorescence imaging confirms effective renal accumulation of Cy5.5-labeled Fe@Ba nanozyme. In vivo experiments show the nanozyme reduces inflammation and significantly enhances survival rates in AKI models.DiscussionThis study validates the concept of self-assembling nanozymes for AKI treatment and offers new insights into nanomedicine applications. The Fe@Ba nanozyme's ability to counteract inflammation-related damage and inhibit ferroptosis through multiple mechanisms highlights its therapeutic potential. The successful integration of traditional Chinese medicine components with nanotechnology represents an innovative approach to addressing cisplatin-induced AKI, suggesting broader applications for metal-polyphenol nanozymes in oxidative stress-related kidney diseases.